2021
DOI: 10.3390/healthcare9040466
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Difficulties, and Coping of Infertile Women

Abstract: The present study aims to highlight how women perceive and adapt to infertility difficulties. To better understand the difficulties that women diagnosed with infertility are experiencing, the study explores this concept in correlation with anxiety and coping. 240 women with fertility problems from various parts of Romania completed the State-Trait Anxiety Inventory (STAI-Form Y), Brief COPE and the scale “Difficulties With Infertility and Its Treatment.” Statistical analyzes showed that women who were at the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…The selection of strategies for coping with the problem of infertility, in addition to gender, turns out to be related to the level of perceived stress and the perception of infertility as a loss or as a challenge. Women struggling with the problem of infertility experience high anxiety, uncertainty and lack of control (Dana, Narimani, Mikaeili, 2013;Yazdani, Kazemi, Fooladi, & Samani, 2016), which is associated with more frequent use of avoidance strategies, self-blame, denial and distraction (Gourounti et al, 2012, Iordăchescu et al, 2021, Zurlo, Della Volta, Vallone, 2020 and perceiving the problem of infertility as a loss (Kalus, 2014). Also, infertile men with higher levels of stress most often adopted blame and avoidance strategies (Babore, Stuppia, Trumello, Candelori, Antonucci, 2017, Nagórska, Obrzut, Ulman & Darmochwał-Kolarz, 2021.…”
Section: Coping Strategies With Infertility or Miscarriagementioning
confidence: 99%
“…The selection of strategies for coping with the problem of infertility, in addition to gender, turns out to be related to the level of perceived stress and the perception of infertility as a loss or as a challenge. Women struggling with the problem of infertility experience high anxiety, uncertainty and lack of control (Dana, Narimani, Mikaeili, 2013;Yazdani, Kazemi, Fooladi, & Samani, 2016), which is associated with more frequent use of avoidance strategies, self-blame, denial and distraction (Gourounti et al, 2012, Iordăchescu et al, 2021, Zurlo, Della Volta, Vallone, 2020 and perceiving the problem of infertility as a loss (Kalus, 2014). Also, infertile men with higher levels of stress most often adopted blame and avoidance strategies (Babore, Stuppia, Trumello, Candelori, Antonucci, 2017, Nagórska, Obrzut, Ulman & Darmochwał-Kolarz, 2021.…”
Section: Coping Strategies With Infertility or Miscarriagementioning
confidence: 99%
“… 9–11 Research from non-Muslim communities also validates that women with infertility are more likely to suffer poor emotional outcomes on their health including increased levels of stress, anxiety, and depression symptoms. 12 …”
Section: Introductionmentioning
confidence: 99%
“…ART can be a means to achieve parenting, but the rate of success is limited and may lead to frustrating couples’ expectations, with high rates of failure around 75%, such as is the case of in vitro fertilization (IVF) [ 8 ]. Therefore, an effective adjustment to involuntary childlessness and infertility should be grounded on coping skills to overcome the hardness of consecutive failed treatments [ 9 , 10 ]. Indeed, a previous review of empirical evidence reported that relational and personal issues and psychological burdens were responsible for individuals’ treatment discontinuation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%